Catalytic Synthesis of Indolines by Hydrogen Atom Transfer to Cobalt(III)–Carbene Radicals - Karns, Alexander S.; Goswami, Monalisa; de Bruin, Bas (Chemistry : a European journal, 2018)
We report a new method for the synthesis of indolines from o‐aminobenzylidine N‐tosylhydrazones proceeding through a cobalt(III)–carbene radical intermediate. This methodology employs the use of inexpensive commercially available reagents and allows for the transformation of easily derivatized benzaldehyde‐derived precursors to functionalized indoline products. This transformation takes advantage of the known propensity of radicals to undergo rapid intramolecular 1,5‐hydrogen atom transfer (1,5‐HAT) to form more stabilized radical intermediates. Computational investigations using density functional theory identify remarkably low barriers for 1,5‐HAT and subsequent radical rebound displacement, providing support for the proposed mechanism. We explore the effect of a variety of nitrogen substituents, and highlight the importance of adequate resonance stabilization of radical intermediates to the success of the transformation. Furthermore, we evaluate the steric and electronic effects of substituents on the aniline ring. This transformation is the first reported example of the synthesis of nitrogen‐containing heterocycles from cobalt(III)–carbene radical precursors. A radical new method for indoline synthesis exploits the propensity of cobalt(III)‐carbene radicals to facilitate 1,5‐hydrogen atom transfer. This article discusses reaction optimization, highlights scope and limitations, and provides computational support for the proposed mechanism.